Front Cover: Vibrational Circular Dichroism Unravels Supramolecular Chirality and Hydration Polymorphism of Nucleoside Crystals (Chem. Eur. J. 63/2022). Issue 63 (31st October 2022) - Krupová, Monika; Leszczenko, Patrycja; Sierka, Ewa; Emma Hamplová, Sára; Pelc, Radek; Andrushchenko, Valery
Abstract : Crystal City in a chiral world : The Crystal City is illuminated by chiral suns shining left‐circularly polarized light (L‐CPL) or right‐circularly polarized light (R‐CPL). The light of the two suns interacts with the skyscraper crystals differently revealing differences in their inner crystal structure. More information can be found in the Research Article by V. Andrushchenko and co‐workers. (DOI: 10.1002/chem.202201922 ). Image designed by Tomáš Belloň at IOCB Prague.